Estimation of genetic variability and association studies for yield in the OsPSTOL1 gene introgressed F4 in rice (Oryza sativa L.) for phosphorus deficiency tolerance - Aananthi, N; Mohamed, Y S K; Arumugam, P M; Shoba, D; Manikandan, K; Nirubana, V; Ramalingam, J; Raiza, C G (Plant Science Today, 2025)
In India, nearly 85 % of the soils are phosphorus-deficient, significantly limiting rice production. Yield improvement based solely on phenotypic selection is challenging due to its polygenic control. This study aimed to identify superior segregants with high yield potential and phosphorus deficiency tolerance. During the Rabi season of 2020, an F4 population derived from the cross Anna (R) 4 × IR 64 Pup1 was evaluated under a non-replicated trial at the Agricultural College and Research Institute, Killikulam. Observations were recorded for eight biometrical traits. A high magnitude of variability was observed among the genotypes, as indicated by high mean values and a wide range for all studied traits. Phenotypic coefficient of variation (PCV) was higher than genotypic coefficient of variation (GCV), signifying environmental influence, while high heritability was observed for most traits. Traits such as the number of tillers per plant, number of productive tillers per plant, number of filled grains per panicle, phosphorus content in shoot, hundred-seed weight and single-plant yield exhibited high heritability coupled with high genetic advance as a percentage of the mean, indicating the predominance of additive gene action, thus making selection effective. Correlation analysis revealed that days to 50 % flowering, number of tillers per plant and panicle length had a strong positive association with grain yield per plant, suggesting their significance in yield improvement. Path analysis indicated that panicle length (0.3012) had the highest positive direct effect on grain yield per plant, followed by phosphorus content in shoot (0.2366), number of productive tillers per plant (0.1965), hundred-seed weight (0.1623) and number of filled grains per panicle (0.1423), while acid phosphatase (-0.172) and number of tillers per plant (-0.0923) had negative direct effects. Based on the overall evaluation, eleven superior families (AI-17, AI-15, AI-19, AI-16, AI-84, AI-64, AI-53, AI-71, AI-82, AI-48 and AI-11) were identified for further breeding programs aimed at improving phosphorus starvation tolerance in rice.